Novel smart yolk/shell polymer microspheres as a multiply responsive cargo delivery system - Du, Pengcheng (Langmuir : the ACS journal of surfaces and colloids, 2014)
An effective strategy was developed to fabricate the novel dually thermo- and pH-responsive yolk/shell polymer microspheres as a drug delivery system (DDS) for the controlled release of anticancer drugs via two-stage distillation precipitation polymerization and seed precipitation polymerization. Their pH-induced thermally responsive polymer shells act as a smart "valve" to adjust the diffusion of the loaded drugs in/out of the polymer containers according to the body environments, while the movable P(MAA-co-EGDMA) cores enhance the drug loading capacity for the anticancer drug doxorubicin hydrochloride (DOX). The yolk/shell polymer microspheres show a low leakage at high pH values but significantly enhanced release at lower pH values equivalent to the tumor body fluid environments at human body temperature, exhibiting the apparent tumor-environment-responsive controlled "on-off" drug release characteristics. Meanwhile, the yolk/shell microspheres expressed very low in vitro cytotoxicity on HepG2 cells. Consequently, their precise tumor-environment-responsive drug delivery performance and high drug loading capacity offer promise for tumor therapy